Digestibility of Dry Matter and Nutrients from Azolla pinnata by Labeo calbasu (Hamilton, 1822) with a Note on Digestive Enzyme Activity - Gangadhar, B.; Umalatha, H.; Hegde, G.; Sridhar, N. (Fishery Technology, 2017)
Digestibility of feed ingredients in the compoundeddiet is an important factor affecting the growth offish. A study was conducted in indoor plastic tubsto estimate the in vivo digestibility of dry matter andnutrients by a minor carp Labeo calbasu for a nonconventionalfeed ingredient – azolla, incorporatedat levels ranging from 0-40% using crude fibre asthe marker. The activities of major digestiveenzymes were also estimated in the gut of fish fedvaried levels of azolla. The digestibility values werethe highest (p